Childhood Experiences and Needs: Parental Goals, Mistakes, and Personality Traits and Their Adult Daughters' Ability to Meet Their Needs - Agnieszka Szymańska; Joanna Świderska (Ignatianum University Press, 2023)
Objectives of the research:. The purpose of this study was to determine whether women's childhood experiences are related to their ability to meet their needs in adulthood. Research methods: The survey was conducted online with a random sample of 402 women between the ages of 21 and 50. In order to answer the research questions, text mining algorithms and cluster analysis carried out by data mining algorithms were used. A short description of the context of the issue: The ability to fulfill one's needs is an important determinant of personal happiness, well-being and mental health The study examined whether women who had experienced fewer parental mistakes were better at meeting their needs, and whether there were intergroup differences between women who were more and less efficient at fulfilling their needs in terms of the personality traits their parents tried to mold in them during childhood and the personality traits that the women developed. Research findings: The results revealed that women who experienced fewer parenting errors in childhood and whose parents tried to shape in them personality traits such as Stability (Alpha-Plus), Plasticity (Beta-Plus) and Integration (Gamma-Plus) indeed developed these traits and were more effective in fulfilling their needs in adulthood. Conclusions and recommendations: Experiencing more parenting mistakes in childhood is associated with the development of unfavorable personality traits and lower competence in meeting needs in adulthood.